EMPOWERING WOMEN, HOW IS THE POINT OF VIEW OF THE ISLAMIC PERSPECTIVE AND LOCAL WISDOM? - DIANIDZA ARODHA (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2026)
Women's empowerment has become a crucial issue in achieving sustainable development, particularly in Muslim communities where religious values and local cultural traditions strongly influence social and economic practices. This study aims to examine how Islamic perspectives and local wisdom contribute to women's empowerment in Bondowoso Regency, East Java, Indonesia. The research employed a qualitative approach with a case study design to explore women's experiences in economic, social, and community development activities. Data were collected through in-depth interviews, participant observation, and document analysis involving Muslim women, religious leaders, community leaders, and local empowerment facilitators. Data validity was ensured through source triangulation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that women's empowerment in Bondowoso is strengthened by the integration of Islamic values, including amanah (trustworthiness), ta'awun (mutual assistance), ukhuwah (solidarity), and maslahah (public welfare), with local wisdom characterized by kinship networks, mutual cooperation, indigenous knowledge, and community-based economic traditions. Women actively participate in agriculture, livestock management, small-scale enterprises, religious organizations, and social activities that contribute to household welfare and community resilience. The study also identifies the TENGKA model (Trust, Effort, Networking, Keeping, and Active Participation) as an effective framework for understanding empowerment processes within Madurese Muslim communities. The integration of Islamic principles and local wisdom enhances social capital, leadership capacity, economic resilience, and environmental sustainability. Therefore, women's empowerment programs should incorporate culturally embedded and faith-based approaches to achieve inclusive and sustainable community development.